Likelihood of Normal ABI Increases With Physiologic Testing Referrals From Rural Primary Care Physicians. Issue 3 (September 2019) - Scissons, Robert P.; Ettaher, Abraham; Afridi, Sophia
Disparities in diagnostic capabilities have been noted between rural and urban health care facilities. We believe the clinical evaluation of peripheral arterial disease (PAD) by rural physicians may be similarly affected. Patients referred for arterial physiologic testing in an urban and rural regional health care network for a consecutive 7-month period were reviewed. Patients were classified into 3 groups based on referring physician specialty: (1) vascular surgeon or vascular medicine specialist (Vasc), (2) urban primary care physician (Urban), and (3) rural primary care physician (Rural). Normal patients were defined by a posterior tibial (PT) or dorsalis pedis (DP) ankle-brachial index (ABI) of ⩾0.90, bilaterally. Abnormal patients had both PT and DP ABI <0.90 in one or both extremities. Group comparisons were made for normal and abnormal patients, age (⩾65 years old), and gender. Patients with history of amputations, angioplasty, bypass graft, stent, calcification (PT or DP ABI ⩾1.30), and previous physiologic testing outside the designated period of analysis were considered a separate subclassification and analyzed separately. Emergency room referrals, inpatients, and patients with incomplete examination data were excluded from the analysis. A total of 430 patient exams were evaluated. Group-Rural had significantly greater numbers of normal ABI patients compared with Group-Urban ( P = .0028) and Group-Vasc ( P = .0000). No significant differences were noted between all groups for age and gender. Substantial disparities were noted in normal and abnormal ABI patients between rural health care physicians and their urban primary care and vascular specialist counterparts. Significantly greater numbers of normal ABI referrals by rural primary care physicians may warrant enhanced PAD diagnosis education or telemedicine alternatives.